ВЗГЛЯД КЛИНИЦИСТА НА ДЕГУМАНИЗАЦИЮ ОТНОШЕНИЙ «ВРАЧ ПАЦИЕНТ» - В. М. Яковлев; А. В. Ягода (SINAPS LLC, 2013)
Today medical literature rarely discusses medical ethics. We do not consider the causes of loss of interest in such an important position of social humanism of modern medicine, as main purpose of our study is the differentiated assessment of the situation today - trend of dehumanizing doctor and patient relationship.